Micro and nanorobot-based drug delivery: an overview. (21st April 2022) - Suhail, Muhammad; Khan, Arshad; Rahim, Muhammad Abdur; Naeem, Abid; Fahad, Muhammad; Badshah, Syed Faisal; Jabar, Abdul; Janakiraman, Ashok Kumar
Abstract: Progress in the drug delivery system in the last few decades has led to many advancements for efficient drug delivery. Both micro and nanorobots, are regarded as superior drug delivery systems to deliver drugs efficiently by altering other forms of energy into propulsion and movements. Furthermore, it can be advantageous as it is directed to targeted sites beneath physiological environments and conditions. They have been validated to possess the capability to encapsulate, transport, and supply therapeutic contents directly to the disease sites, thus enhancing the therapeutic efficiency and decreasing systemic side effects of the toxic drugs. This review discusses about the microand nanorobots for the diagnostics and management of diseases, types of micro, and nanorobots, role of robots in drug delivery, and its biomedical applications.